Characteristics of the flow regime along the regulated Tisza river reach downstream of Tiszafüred - Bezdán, Mária (Journal of Environmental Geography, 2010)
An attempt is presented at clearing the reasons of some uncommon flow phenomena observed over the Tisza reach downstream of Tisza-füred and at pointing to the practical significance of the results ob-tained. Over six hundred thousand daily stage data were selected from the more than six million (!) water levels registered form 1876 to 2009 (on the gauges between Tiszafüred and Novi Be?ej (Törökbecse)). Drawing also on the data of ground water wells, the conclusions ar-rived at are believed to be of interest to theoretical fluvial hydrologists, yet also to river engineers engaged in designing and operating (when needed) flood control schemes.